RANCANG BANGUN SISTEM INFORMASI PENJUALAN LAYANAN SOCIAL MEDIA MANAGEMENT PERUSAHAAN SOLUTIVE DENGAN MENGGUNAKAN MODEL WATERFALL - Pramono, Teguh Dwi; Syahminan; Setiyaningsih, Wiji (Department of System Information, 2025)
The Solutive company is currently facing several issues in its sales process, including time-consuming transactions that are still conducted directly at the office and manual record-keeping using Microsoft Excel, which complicates sales data coordination. The aim of this research is to use the waterfall method to develop a sales information system for social media services at Solutive, with the goal of facilitating customer transactions and providing a sales reporting system for Solutive's Social Media Management services. Based on the research conducted, a UAT application test was performed, divided into three assessment criteria, with the system aspect achieving a percentage of 89.75%, the user aspect obtaining a percentage of 91.33%, and the interaction aspect reaching a percentage of 92.91%. The average percentage of the UAT test reached 91.33%. From the results of the UAT test, it can be concluded that the performance of the Solutive company's Social Media Management Service Sales Information System is rated as very good.